Kelvin‐Helmholtz wave at the subsolar magnetopause boundary layer under radial IMF. Issue 10 (25th October 2016) - Grygorov, K.; Němeček, Z.; Šafránková, J.; Přech, L.; Pi, G.; Shue, J.‐H.
Abstract: We present the first observation of the Kelvin‐Helmholtz (KH) rolled‐up vortex at the dayside magnetopause layers under a radial interplanetary magnetic field (IMF). The study uses measurements of four Time History of Events and Macroscale Interactions during Substorms (THEMIS) probes aligned along the Y GSE axis about 10 R E upstream of the Earth and located in different regions of the near‐Earth environment. THEMIS C and A serve as monitors of the quiet solar wind and fluctuating magnetosheath conditions, respectively, and THEMIS D and E observe the magnetopause and low‐latitude boundary layer (LLBL) crossings. The analysis shows the following: (1) a radial IMF changes to the southward pointing magnetosheath magnetic field; (2) dayside reconnection forms the thin but dense LLBL; (3) a large velocity shear at the LLBL inner edge excites a train of KH waves; and (4) in spite of a short path from the subsolar point (≈5 R E ), one of the KH waves exhibits all features of a fully developed rolled‐up vortex. Key Points: Radial IMF converted to the southward field at the magnetopause Observations of well‐developed Kelvin‐Helmholtz vortex near the subsolar point Simultaneous action of KH instability and reconnection creates the thick LLBL